Comparison of the Views of Classical Fiqh Ulama and Contemporary Fiqh Ulama on the Use of Zakat Maal for the Development of Educational and Da'wah Institutions - Fikriyah, Khusnul (UIN Sunan Kudus, 2021)
Nowadays, zakat paid by muzakki is channeled through an educational empowerment model, including scholarships for poor children. In addition to scholarships, the empowerment model also improved, zakat funds are also used for the development of Educational and Da'wah Institutions, including for schools, campuses, dormitories, and mosques. In At-Taubah 60, there is no mention of the Board of Education and Da'wah included in the asnaf who are entitled to receive zakat. Thus, the question arises as to how the legal position of the use of zakat funds for the benefit of the development of educational institutions and da'wah, whether the law is allowed according to sharia or not. This study used a qualitative library research method. The conclusion of this article states that zakat funds are allowed for the construction of educational and da’wah institutions, by using the reason for the